2008
DOI: 10.1248/cpb.56.642
|View full text |Cite
|
Sign up to set email alerts
|

New Lanostane Triterpene Lactones from the Vietnamese Mushroom Ganoderma colossum (FR.) C. F. BAKER

Abstract: Four new lanostane triterpene lactones (colossolactone I, colossolactone II, colossolactone III and colossolactone IV) were isolated from the Vietnamese mushroom Ganoderma colossum (FR.) C. F. BAKER along with five known compounds. The structures of the new compounds were determined on the basis of MS, NMR and circular dichroism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Methyl lucidenate H (methyl 3β, 7β-dihydroxy-4α-hydroxymethyl-4β, 14α-dimethyl-11,15-dioxo-5α-chol-8-en-24-oate) G. lucidum (fruit bodies) [64] 264 Methyl lucidenate I (3β-hydroxy-4α-hydroxymethyl-4β, 14α-dimethyl-7,11,15-trioxo-5α-chol-8-en-24-oate) G. lucidum (fruit bodies) [64] 265 Methyl lucidenate J (3β, 12β-dihydroxy-4α-hydroxymethyl-4β, 14α-dimethyl-7,11,15-trioxo-5α-chol-8-en-24-oate) G. lucidum (fruit bodies) [64] 266 Methyl lucidenate Ha G. sinense (fruit bodies) [47] 267 Colossolactone I ((22S)-3-β-hydroxylanosta-8,24-dien-26,22-olide) G. colossum [97] 268 Colossolactone II ((22S)-1,3-β-dihydroxylanosta-8,24-dien-26,22-olide) G. colossum [97] 269 Colossolactone D G. colossum (fruit bodies) [98] 270 Colossolactone E G. colossum (fruit bodies) [98] 271 Colossolactone F G. colossum (fruit bodies) [98] 272 Colossolactone G G. colossum (fruit bodies) [98] 273 Ganosporelactone A G. lucidum (spores) [99] 274 Ganosporelactone B G. lucidum (spores) [99] 275…”
mentioning
confidence: 99%
“…Methyl lucidenate H (methyl 3β, 7β-dihydroxy-4α-hydroxymethyl-4β, 14α-dimethyl-11,15-dioxo-5α-chol-8-en-24-oate) G. lucidum (fruit bodies) [64] 264 Methyl lucidenate I (3β-hydroxy-4α-hydroxymethyl-4β, 14α-dimethyl-7,11,15-trioxo-5α-chol-8-en-24-oate) G. lucidum (fruit bodies) [64] 265 Methyl lucidenate J (3β, 12β-dihydroxy-4α-hydroxymethyl-4β, 14α-dimethyl-7,11,15-trioxo-5α-chol-8-en-24-oate) G. lucidum (fruit bodies) [64] 266 Methyl lucidenate Ha G. sinense (fruit bodies) [47] 267 Colossolactone I ((22S)-3-β-hydroxylanosta-8,24-dien-26,22-olide) G. colossum [97] 268 Colossolactone II ((22S)-1,3-β-dihydroxylanosta-8,24-dien-26,22-olide) G. colossum [97] 269 Colossolactone D G. colossum (fruit bodies) [98] 270 Colossolactone E G. colossum (fruit bodies) [98] 271 Colossolactone F G. colossum (fruit bodies) [98] 272 Colossolactone G G. colossum (fruit bodies) [98] 273 Ganosporelactone A G. lucidum (spores) [99] 274 Ganosporelactone B G. lucidum (spores) [99] 275…”
mentioning
confidence: 99%
“…The 13 C NMR and DEPT spectra of 1 (Table 1) displayed 31 carbons ascribable to nine quaternary carbons (one carbonyl at d C 167.1 and four olefinic at d C 149.1, 134.7, 134.0, and 122.0), five methines (two oxygenated at d C 79.0 and 78.6), nine methylenes, and eight methyls. The 1 H and 13 C NMR spectroscopic data of compound 1 resembled those of a known lanostane-type triterpenoid lactone, colossolactone I (El Dine et al, 2008), suggesting a lanostane-type triterpenoid skeleton for 1. A detailed comparison of the UV, IR, and NMR data for the two closely related compounds demonstrated that compound 1 differed from colossolactone I by having an a,b-dimethyl, a,bunsaturated d-lactone side-chain moiety with one additional methyl group at C-24, which was confirmed by analysis of the HMBC correlations (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…The relative configurations at C-3, C-5, C-10, C-13, C-14, C-17, and C-20 of 1 were determined as shown in Fig. 1 based on a biogenetic consideration of the lanostane skeleton (Li and Du, 2008) (Chen et al, 1999;El Dine et al, 2008;Taji et al, 2008). The b-orientation of the hydroxy group at C-3 was deduced from the multiplicities of H-3 (d H 3.23 (dd, 11.5, 4.5 Hz)) (El Dine et al, 2008) and a strong NOE correlation between H-3 and H-5.…”
Section: Resultsmentioning
confidence: 99%
“…The stereochemistry at C-22 of colossolactone V (24) was determined as R, by using Mosher ester methodology after deacetylation of the alcohol. Comparisons with the CD spectra of colossolactones V (24) and VI (25), determined that the configuration of C-22 in 25 was also R [41][42]. All of the isolated compounds except for 22, 25, 28, and 31, dose-dependently inhibited HIV-1 protease ( Table 2) Ganoderma sinense is registered in the Chinese Pharmacopoeia together with G. lucidum under the name "Ling Zhi" as a traditional Chinese medicine.…”
Section: Ganoderma Triterpenes and Their Derivativesmentioning
confidence: 97%
“…In contrast to G. lucidum, little is known about the chemical constituents of G. sinense. Our phytochemical analysis of G. sinense led to the isolation and structural determination of three new triterpene-farnesyl hydroquinone conjugates (35)(36)(37) and five new highly oxygenated lanostane-type triterpenoids (38)(39)(40)(41)(42) from the fruiting body of this medicinal mushroom. The structures of the new compounds were determined from spectroscopic data and they were named ganosinensins A−C (35−37), ganoderic acid GS-1 (38) (47), ganoderiol F (48), cerevisterol, 5,6-dihydroergosterol and ergosterol peroxide were also isolated [43][44].…”
Section: Ganoderma Triterpenes and Their Derivativesmentioning
confidence: 99%